Efficacy of Leflunomide, Telmisartan, and Clopidogrel for Immunoglobulin A Nephropathy: A Randomized Controlled Trial - Wu, Jie (Chin Med J (Engl), 2016)
BACKGROUND: The efficacy and safety of telmisartan combined with clopidogrel, leflunomide, or both drugs for immunoglobulin A nephropathy (IgAN) are unclear. This study was designed to evaluate the efficacy and safety of telmisartan combined with clopidogrel, leflunomide, or both drugs for IgAN. METHODS: It is a multicenter, prospective, double-dummy randomized controlled trial. Primary IgAN patients were recruited in 13 renal units across Beijing, China, from July 2010 to June 2012. After a 4-week telmisartan (80 mg/d) wash-in, 400 patients continuing on 80 mg/d telmisartan were randomly assigned to additionally receive placebo (Group A), 50 mg/d clopidogrel (Group B), 20 mg/d leflunomide (Group C), or 50 mg/d clopidogrel and 20 mg/d leflunomide (Group D). The 24-week intervention was completed by 360 patients. The primary endpoint was change in 24-h proteinuria at 24 weeks. A linear mixed-effect model was used to analyze the changes at 4, 12, and 24 weeks. Generalized estimating equations were used to evaluate changes in hematuria grade. This trial was registered at the Chinese Clinical Trial Registry. RESULTS: The effects of telmisartan combined with leflunomide on changes in proteinuria (0.36 [95% confidence interval (CI) 0.18–0.55] g/d, P < 0.001), in serum uric acid (76.96 [95% CI 57.44–96.49] μmol/L, P < 0.001), in serum creatinine (9.49 [95% CI 6.54–12.44] μmol/L, P < 0.001), and in estimated glomerular filtration rate (−6.72 [95% CI −9.46 to −3.98] ml∙min(−1)∙1.73 m(−2), P < 0.001) were statistically significant, whereas they were not statistically significant on changes in systolic and diastolic blood pressure and weight (P > 0.05). Telmisartan combined with clopidogrel had no statistical effect on any outcome, and there was no interaction between the interventions. No obvious adverse reactions were observed. CONCLUSIONS: Telmisartan combined with leflunomide, not clopidogrel, is safe and effective for decreasing proteinuria in certain IgAN patients. TRIAL REGISTRATION: chictr.org.cn, ChiCTR-TRC-10000776; http://www.chictr.org.cn/showproj.aspx?proj=8760.